(untitled) (Journal of Informatics and Mathematical Sciences, 2019)
The goal of this paper is to review about the dynamical behavior of the positive solutions of the systems of difference equations. The present study gives review of recent studies in systems of difference equations. We focus on papers dealing with two-dimensional, third-dimensional and multi-dimensional systems of nonlinear difference equations.